Spinal biopsies: a clinicopathologic review of 53 cases diagnosed between 2011 and 2018 at a tertiary hospital in Kampala, Uganda - James J. Yahaya (SpringerOpen, 2021)
Abstract Background Early diagnosis of spinal cord neoplasia serves patients from developing a number of complications and even death. Methods After obtaining ethical approval, retrospectively, a total of 53 tissue blocks of patients attended at the spinal ward were reviewed. Statistical analysis was done using SPSS version 20.0, and p value of less than 0.05 was applied to establish the existence of statistical significance between the compared categorical variables. Results The mean age of the patients was 30.7 ± 15.96 years. Most of the patients 32.1% (n = 17) were aged ≤ 19 years, and majority of the neoplasia 77.3% (n = 41) were extramedullary. Also, majority of the neoplasia 60.4% (n = 32) were benign and the malignant ones were 35.8% (n = 19). The mean duration of onset of symptoms for benign and malignant neoplasia in this study was 13.1 ± 16.4 and 3.4 ± 2.8 years, respectively, with statistical difference (95% CI 2.09–17.35, p = 0.014). Conclusion The patients with spinal cord neoplasia in the present study were of young age, and majority of them had benign neoplasia that were extramedullary located. The mean duration of onset of symptoms for patients with malignant neoplasia was significantly shorter than that of benign neoplasia.